BATHING HABIT AND LIFESTYLE CHANGING BATHROOM DESIGN AND FACILITIES - Pane, Sri Fariyanti (International Review of Humanities Studies, 2020)
Indonesian people to have a habit of cleaning themselves by bathing with cold water. Hot climate and pollution make our activity in a bath twice a day, morning and afternoon or evening. The bathing habits depending on environmental circumstances in which they are located, whether in the village or in the city. Changes affecting the bathing habits of the interior design of a bathroom and shower. The interior design of the house, especially the bathroom and the toilet is required by the city people have different lifestyles with villagers. Social status to be a difference urban life, lifestyle became a standard acknowledgment to upper-income level. Lifestyle change the habits of a shower and bathroom design, as well as supporting facilities. The bathroom becomes a space of relaxation after a full day of activity outside the home. The interior design and product design into healthcare solutions which have the power sanitary technology based on human needs and activities in the bathroom. By using the approach of beauty through the interior design and lifestyle. This study, using qualitative descriptive analysis using literature data, photos, and direct observations in the field.